SISTEM PELAYANAN HAJI PADA KANWIL KEMENTERIAN AGAMA PROVINSI NUSA TENGGARA BARAT - Nashuddin, Nashuddin (JURNAL PENELITIAN KEISLAMAN, 2011)
The study analyzes the pilgrim service system that includes registration, health, manasik of hajj, accommodation, consumption and transportation services. It also attempts to explain the responses of the stakeholders and the constraints faced by the Regional Office of Religious Affairs of West Nusa Tenggara Province in providing services to pilgrim. This is qualitative research that gathers its data through observation, interview and documentation. The study shows that the service of pilgrim provided by the office did not entirely meet with the needs and expectations of the hajj participants. The participants felt that registration, health, catering and accommodation services were all satisfying except for manasik tutoring services and transportation. The study also demonstrates that the hajj service, registration and procedure went fast, simple, open and accessible, making the whole process run easily. To sustain its professionalism in giving the hajj service, the office adopted an integrated principle, which is adaptive and responsive, that make the whole process of pilgrim effective.